2014
DOI: 10.1186/1746-6148-10-14
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with negative in-vivodiagnostic results in bovine tuberculosis-infected cattle in Spain

Abstract: BackgroundDespite great effort and investment incurred over decades to control bovine tuberculosis (bTB), it is still one of the most important zoonotic diseases in many areas of the world. Test-and-slaughter strategies, the basis of most bTB eradication programs carried out worldwide, have demonstrated its usefulness in the control of the disease. However, in certain countries, eradication has not been achieved due in part to limitations of currently available diagnostic tests. In this study, results of in-vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…In addition, there might be risk factors associated with the application of the tests that may influence a negative result even if the animal is truly infected (Alvarez et al, 2014). This situation is particularly problematic in endemic regions or in herds where bTB is chronic because there is a risk of leaving residual infection, making it difficult for a herd to clear infection (Conlan et al, 2012;Gallagher et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, there might be risk factors associated with the application of the tests that may influence a negative result even if the animal is truly infected (Alvarez et al, 2014). This situation is particularly problematic in endemic regions or in herds where bTB is chronic because there is a risk of leaving residual infection, making it difficult for a herd to clear infection (Conlan et al, 2012;Gallagher et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Breed (Brooks-Pollock et al, 2013), age (Brooks-Pollock et al, 2013;Alvarez et al, 2014), and the individual variability of the animals (Pollock and Neil, 2002;Schiller et al, 2010;Whelan et al, 2010) have been reported as possible host-related causes of an impaired performance of the tests. In addition, the effect of other factors related with the test itself, such as the quality of the PPDs used (Good et al, 2011a,b) and the position where it is inoculated (Monaghan et al, 1994) has been also reported.…”
Section: Introductionmentioning
confidence: 97%
“…The tuberculin tests (SIT and CTT) and γ-IFN assay in cattle were done simultaneously to ensure the reliability of the results as described elsewhere [11]. Based on the test results, the cattle positive to either SIT and γ-IFN assay or CTT and γ-IFN assay was interpreted as positive to BTB.…”
Section: In Vitro γ-Ifn Testmentioning
confidence: 99%